State of-The-Art Multi-Input DC-DC Converter Topologies and their Control Techniques: A Review (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Environmental awareness and technological advancement have made renewable energy sources such as fuel cell,solar photovoltaic (PV), wind energy an emerging research area. Power electronics converters are used as interface betweenthe renewable energy sources and the load unit, aimed at matching these sources with the load demand and improving thesteady-state and dynamic characteristics. Traditional method of using multiple single-input single-output dc-dc converter tointegrate several renewable energy sources, comes with challenges in controller design, poor efficiency, low power densityand increase in cost. To address these limitations, the use of an integrated multi-port converter is a preferable solution.Recently, several multi-port dc-dc converter topologies have been reported each having its peculiarity in terms of number ofcomponent count, relationships between input and output, voltage conversion ratio, control algorithm and efficiency. Thisarticle reviewed multi-port dc-dc converters presented by different research groups from the point of view of topology, inputand output relation and structure. Furthermore, control algorithms proposed to solve various control problems are alsoreviewed.
Keywords: Control techniques; dc-dc converter; multi-input multi-output converters